Editorial - Pacheco Romero, José (2016)
An editorial in the Lancet has been dedicated to the unprecedented increase in longevity in the world, which means a "progressive dividend investment in health and ocioeconómicas policies." This will relate to challenges and opportunities in education, organization and health care of the long-lived. They will be key to take into account the basic needs aspects, autonomy, mobility, relations and the contribution of long-lived society, which involves new government policies and societal attitudes that influence the physical and mental capacity of people old. Apart from housing to affordable, safe and accessible, it should be borne in mind transport, cultural and community activities, opportunities for physical activity, and avoiding exposure to snuff and other harmful agents. The article refers to is not imaginable provide equitable quality care to the elderly person in the absence of universal health coverage, as well as some form of social support integrated and economically affordable. The message is relevant for all professionals and health systems, especially in middle and low income countries where, by 2050, will live 80% of people older than 60. At present only one country, Japan, has already more than 30% of its population older than 60 years. By 2050, there will be many other countries, including Chile, China, Iran, Thailand (1), it is quite possible, Peru.